Distribution of dwarfing genes Rht-B1b and Rht-D1b in Indian wheat (Triticum aestivum) cultivars detected by functional markers - SHEORAN, S; SINGH, V; MALIK, R; KUNDU, S; TIWARI, R; KUMAR, R; SHORAN, J (The Indian Journal of Agricultural Sciences, 2026)
The present study was conducted to determine the frequency of allelic variations for Rht-B1b and Rht-D1b in wheat(Triticum aestivum L.) cultivars grown in different agro-climatic zones of India and to investigate the agronomic performance (plant height, average yield, no. of spikelets/spike, no. of seeds/spike and 1 000 grain weight) with allelic variants of Rht genes. One hundred Indian wheat varieties released during the period of 1968-2006 were screened with PCR based STS marker for Rht-B1b and Rht-D1b. Rht-B1b allele predominates in the North Western Plains Zone of India with a frequency of 25%. Rht-D1b was found in the 15% of the cultivars which are mainly cultivated in Central Zone. None of the dwarfing allele had been found in the cultivars of Northern Hills Zone. Cultivars having Rht-B1b allele had significantly highest average yield than wheat genotypes without any of these dwarfing allele. Rht-B1b+Rht-D1b allele was found in 7% of the cultivars out of the selected ones dominating North Western Plains Zone.